Beyond the Common Core: Examining 20 Years of Literacy Priorities and Their Impact on Struggling Readers. Issue 2 (2nd April 2016) - Cassidy, Jack; Ortlieb, Evan; Grote-Garcia, Stephanie
ABSTRACT: Researchers utilized a historical context of the What's Hot, What's Not expert surveys over the last 20 years to examine literacy priorities and possible impacts. The Common Core State Standards (CCSS) were recently recognized as the hottest topic in the field of literacy education. Perhaps one of the unintended consequences of this intense focus is that literacy priorities have shifted away from other important topics, particularly those involving children and youth who may fail to meet these new rigorous standards. Topics such as early intervention; literacy coaches/reading specialists; motivation/engagement; response to intervention/differentiated instruction; and struggling readers have not been as highly rated as in the past, yet perhaps should warrant more attention if all students are expected to be college or career ready. This article takes the stance that rigorous standards alone are not enough. A historical context is provided and discussed regarding how these topics related to less proficient readers gained traction in schools, what contributed to their demise, and how a reexamination of literacy priorities and a revival of these topics might contribute to productive pedagogies and subsequent literacy growth in the era of CCSS.